Application of the RPN methodology for quantification of the operability of the quadruple-tank process - Trierweiler,J.O. (2002)
The RPN indicates how potentially difficult it is for a given system to achieve the desired performance robustly. It reflects both the attainable performance of a system and its degree of directionality. Two new indices, RPN ratio and RPN difference are introduced to quantify how realizable a given desired performance can be. The predictions made by RPN are verified by closed-loop simulations. These indices are applied to quantify the IO-controllability of the quadruple-tank process.